Detection and Isolation of the Repressor Protein for the Tryptophan Operon of Escherichia coli - Zubay, G. (1972)
DNA from a transducing bacteriophage carrying a fusion of the tryptophan and lactose operons of E. coli (λdtrp-lac) has been used to direct cell-free synthesis of β-galactosidase (EC 3.2.1.23). Whereas normal lac operon (λdlac) DNA requires adenosine-3′:5′-cyclic monophosphate (cAMP) for β-galactosidase synthesis, trp-lac DNA is unaffected by cAMP. This difference in cAMP dependence verifies the presence of a cAMP-requiring promoter in the lac operon that has been removed from the trp-lac DNA. Synthesis with trp-lac DNA is controlled by the protein product of the tryptophan repressor gene (trpR). Synthesis in extracts of trpR(-) (repressor-negative) cells is progressively reduced by increased additions of extract from trpR(+) cells. No trpR(-) product repression is seen when β-galactosidase synthesis is programmed by normal lac DNA. This highly sensitive and specific assay has facilitated quantitation and partial purification of the trp repressor.